Lanthanum oxide nanoparticles as chemical sensor for direct detection of carboxymethyl cellulose in eye drops. Issue 3 (4th March 2023) - Mamatha, K. M.; Srinivasa Murthy, V.; Ravikumar, C. R.; Murthy, H. C. Ananda; Alam, Mir Waqas; Vinutha, K.; Jahagirdar, A. A.
Abstract: Lanthanum oxide nanoparticles (LONPs) were prepared by the probe sonication method. Various analytical and electrochemical techniques were employed to understand the morphology, crystallinity, and band gap of LONPs. The electrochemical sensing ability of the as synthesized LONPs with the carboxymethyl cellulose material present in the eye drops was investigated. X-ray diffraction (XRD) studies revealed that the NPs exists in a hexagonal lattice with a space group, P321 with a crystallite size ranging between 14 and 17 nm. UV-DRS (diffuse reflectance) spectra was used to arrive at the band gap of 3.54 eV for LONPs. Cyclic voltametric (CV) results presented superior electrochemical properties for LONPs with lower value of ΔEa, c . Carboxymethyl cellulose (CMC) material in eye drops was effectively sensed by LONPs in 0.1 N HCl electrolyte. Electrochemical impedance study corroborated the least charge-transfer resistance value for LONPs, obtained after fitting to the equivalent circuit. The electrochemical behavior confirmed the potential role of LONPs as a promising electrode material for sensing molecule such as CMC.